2017
DOI: 10.1117/1.jrs.11.026034
|View full text |Cite
|
Sign up to set email alerts
|

Using remotely sensed spectral reflectance to indicate leaf photosynthetic efficiency derived from active fluorescence measurements

Abstract: , "Using remotely sensed spectral reflectance to indicate leaf photosynthetic efficiency derived from active fluorescence measurements," J. Appl. Remote Sens. 11(2), 026034 (2017), doi: 10.1117/1.JRS.11.026034. Abstract. Chlorophyll fluorescence (ChlF) is an important signature of photosynthesis to evaluate plant response to the environment. We explored an approach to estimate an important leaf ChlF-derived parameter, the intrinsic efficiency of photosystem II photochemistry (F v ∕F m ), using spectral indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 69 publications
1
17
1
Order By: Relevance
“…The single ratio (SR) and the curvature index (CUR) were highly correlated with F V /F M (Jia et al, 2016). Peng et al (2017) concluded that normalized difference vegetation index (NDVI) correlated with F V /F M only in non-stressed plants. In contrast, other authors reported no significant correlation between NDVI and Chl-F parameters (Jia et al, 2016).…”
Section: Biotic Stress Detection In High-throughput Platforms and At mentioning
confidence: 99%
“…The single ratio (SR) and the curvature index (CUR) were highly correlated with F V /F M (Jia et al, 2016). Peng et al (2017) concluded that normalized difference vegetation index (NDVI) correlated with F V /F M only in non-stressed plants. In contrast, other authors reported no significant correlation between NDVI and Chl-F parameters (Jia et al, 2016).…”
Section: Biotic Stress Detection In High-throughput Platforms and At mentioning
confidence: 99%
“…At the next stage of the work, correlation analysis was performed comparing particular VIs derived from satellite images and those ChlF values measured on the ground in order to find if a significant relationship existed between these two parameters. Assessments of Fv/Fm from VIs derived from remote sensing data have been reported by several studies (Tan et al 2012;Peng et al 2017;Kycko et al 2019a;Kycko et al 2019b;Wei et al 2019;Zagajewski et al, 2017;Zagajewski et al 2018). For instance, some researchers compared the results of VIs to assess the Fv/Fm of maize, and reached the conclusion that out of the various kinds of VI that had a close relationship with Fv/Fm, SIPI performed best (Tan et al, 2012).…”
Section: Resultsmentioning
confidence: 94%
“…Kycko et al (2019a) and Zagajewski et al (2018) used in-situ hyperspectral remote sensing as an important technique to fulfill real-time monitoring of plant condition based on its superior performance in acquiring vegetation canopy information rapidly and non-destructively. In studies conducted by Peng et. al.…”
Section: Resultsmentioning
confidence: 99%
“…The chlorophyll contents and LAI values did not show much difference between the stressed and unstressed plants during the early phase of water stress. Zygielbaum et al () also observed that the water stress during the first 4 days in the maize crop did not change chlorophyll contents, which they attributed to photoprotective capacity of a plant such as chloroplast avoidance mechanism (Peng et al, ; Yamada et al, ; Zygielbaum et al, ). In contrast, the differences in all the physiological parameters (LAI, RWC, and EL) between stressed and unstressed plants continued to increase with the increase in the intensity of stress (as SWP decreased from about −57.4 kPa on 71 DAS to −130.7 KPa on 84 DAS in T 5 ) similar to the widening gaps between stressed and unstressed canopy reflectance values (Figures a–d).…”
Section: Resultsmentioning
confidence: 98%